Case Report: A case of transcatheter aortic valve replacement in a patient with a small aortic annulus using the Acurate Neo2 - Shahzil Abdur Rehman Malik; Jamshed Ali; Maleeha Javed; Kamran Hussain; Navaira Azeem; Nasir Rehman; Osman Faheem (Frontiers in Cardiovascular Medicine)
Small aortic annulus poses a major challenge in aortic valve replacement due to the increased risk of prosthesis–patient mismatch (PPM) and increased surgical risk. In recent years, transcatheter aortic valve replacement (TAVR) has emerged as a popular alternative to the traditional surgical aortic valve replacement. We present the case of an 80-year-old woman with a small aortic annulus who underwent TAVR using a self-expanding transcatheter heart valve Acurate Neo2 after an non-ST-segment elevation myocardial infarction (NSTEMI) presentation. These risks, combined with advanced age, significant co-morbidities, and a severely calcified small aortic annulus, supported the choice of TAVR with a self-expanding Acurate Neo2 valve. Despite multiple risk factors for PPM, the patient had a successful outcome without major complications. Our case highlights the off-label use of the Acurate Neo2 valve in one of the smallest aortic annuli reported to date, showcasing its feasibility in Asian and resource-limited settings.